Evaluation and validation of characterization methods for fatigue performance of asphalt mixes for Western Australia - Nega, Ainalem; Nikraz, Hamid; Leek, Colin; Ghadimi, Behzad (Trans Tech Publications Inc, 2013)
The determination of appropriate pavement thickness using laboratory determined parameters is one of the key issues facing the road manager. Five different types of asphalt mixes were produced in laboratory to modify pavement performance mixture. The main objective of this study is to evaluate the characterization methods for fatigue performance of asphalt mixes to Western Australia road. In this study, laboratory test for indirect tensile modulus, dynamic creep, wheel tracking and aggregate gradation tests were taken to analyze each asphalt mixtures for a design traffic road. The results and analysis showed that AC20-75 asphalt mix blow is the most effective and efficient in pavement performance than the other asphalt mixes. AC14-75 was the second in rank to strengthen and durability of asphalt pavement. All asphalt mixes in this study can be used to strength and stable the overall stiffness of pavement, and modification rank can be described as AC20-75 Blow > AC14-75 Blow > AC14-50 Blow > AC7-50 Blow > SMA7-50 Blow in this research.